Aplikasi Deteksi Ekspresi Wajah Dengan Mesin Learning - Anjani, Nur; Hasnawati, Hasnawati; Sahidin, Sudirman (Jurnal Sintaks Logika, 2024)
Often, humans interact using facial expressions that can reveal emotions as evidence of whether someone is telling the truth or not. This research aims to help identify a person's expressions, such as silence, laughter, and smiling. Research using quantitative methods with Android Studio applications and real-time machine learning, displaying accuracy parameters on expressions. The results show the success of the application in detecting facial expressions and displaying accuracy parameters for expressions such as wide-eyed, closed eyes, smile, neutral, and laughter in real-time.